A Implementation Of Teams Games Tournament Assisted By Educandy To Improve Learning Activities - Muhammad Aqsa Azzikra; A. Zam Immawan Alam; Muh. Rahmat (ALENA : Journal of Elementary Education, 2026)
The problem that student learning activities are low is caused by the use of learning models and media that are not relevant to class needs. This study aimed to analyze the results of implementing the Teams Games Tournament (TGT) learning model, assisted by Educandy educational games, in enhancing student learning activity. This research was a classroom action research involving 24 fifth-grade students from SDN 11/22 Gentung as research subjects. Data collection techniques in this study utilized observation sheets for teacher activity implementation and student learning activity. The data analysis technique for this research was descriptive-qualitative. The research results indicated an increase in student learning activity, which was evident in Cycle I observations with an average of 64% (categorized as less active), and subsequently increased in Cycle II with an average of 88% (categorized as active).